Regulatory Developments on Sustainability Issues in Light of Delegated Regulation (EU) 2023/2772 (ESRS) - Virginia Martínez-Torres (Review of European and Comparative Law)
Sustainability reports have undergone significant evolution with the implementation of Directive 2022/2464 (CSRD). Despite the standardization efforts through the European Sustainability Reporting Standards (ESRS) developed by EFRAG, in 2023, the European Commission proposed significant reductions in reporting requirements, with cuts of up to 50%. This step back in the requirements has caused uncertainty about the CSRD’s ability to ensure effective environmental sustainability reporting. The changes, formalized in Delegated Regulation (EU) 2023/2772, represent a turning point in regulating corporate sustainability, and their adequacy in achieving transparency and comparability objectives continues to be a matter of debate.